Distribution of cold and temperate ice and water in glaciers at Nordenskiöld Land, Svalbard, according to data on ground-based radio-echo sounding - Macheret, Yuri; Glazovsky, Andrey; Lavrentiev, Ivan (Bulletin of Geography. Physical Geography Series, 2019)
The distribution of cold and temperate ice and water in polythermal glaciers is an important characteristic in studying their thermal regime, hydrology, and response to climate change. Data analysis of ground-based radio-echo sounding of 16 glaciers in Nordenskiöld Land in Spitsbergen shows that 4 of them are of cold type and 12 are of polythermal type. The mean thickness of cold and temperate ice in polythermal glaciers varies from 11±2 to 66±6 m and from 6±2 to 96±9 m, respectively, and their ratio varies from 0.30 to 5.31. The volume of temperate ice in polythermal glaciers varies from 0.0009 to 3.733 (±10%) km3. With water content of 2% in temperate ice in these glaciers they might contain in total up to 93.5 × 106 m3 of liquid water. Radar data suggest the greater water content or greater size of water inclusions in near-bottom temperate ice.